Familial myelodysplastic syndrome/acute myeloid leukemia - Churpek, Jane E. (Best Pract Res Clin Haematol, 2017)
A growing number of inherited genetic loci that contribute to myelodysplastic syndrome/acute myeloid leukemia (MDS/AML) development in both children as well as adults are rapidly being identified. In recognition of the clinical impact of this emerging field, the World Health Organization, National Comprehensive Cancer Network, and European LeukemiaNet have all added consideration of inherited predisposition to MDS/AML classification and management. Study of these disorders is providing unique insight into the biology of both sporadic and familial MDS/AML. International collaborative efforts to store germline tissue, document family histories, and pool data are essential to progress in diagnosing and treating both hereditary and sporadic forms of MDS/AML.